The Aesthetics of Infrastructure:: Reflections on the Scale Models of the TVA - Colangelo, Jessica; Sharpless, Charles (ARCC Conference Repository, 2019)
Recognizing the importance of aesthetics in the contemporary discussion on infrastructure design, this paper looks to the work of Tennessee Valley Authority (TVA) as a historical case study that successfully merged a strong aesthetic agenda within an infrastructure project. The structures of the TVA have been extensively published in architectural journals and popular magazines for their innovation in dam design, modern appearance and ability to incorporate humanist values within a large-scale infrastructure project. Often discussed through the grand vision of the Chief Architect, Roland A. Wank, less attention has been focused on the specific project methods utilized in the collaboration of the architects and engineers of the TVA. With research collected from the National Archive at Atlanta, this paper explores the role that scale models play in the design process of the TVA during the design and construction of Norris Dam. For architects, the scale model is an important tool for the testing and communicating a project’s design intentions. However as is common in the world of architecture, the model is more than a utilitarian tool, often gaining the status of an aesthetic object that exists in its own right outside of the project for which it was intended to describe. While the production and reception of architecture models comes with its own extensive history and theorization, this paper looks specifically at the models that were built for a large-scale infrastructure as the site in which an aesthetic project that could be initiated by the architect is adopted within the working process of a large collaborative design team.